Effect of Taxes on Capital and Labor in Colombia: A Computable General Equilibrium Analysis (2020)
Using a computable general equilibrium model, calibrated for Colombia, it is analyze theimpact of various economic policies, which affect the relative price of production factors.The results concluded that the incentives for investment, which can be interpreted asactions that decrease the cost of capital, however lead to the accumulation of capital,and thereby increase the productivity of labour, generating net positive effects onemployment. The Elimination of the payroll taxes, for its part, generates a reduction inthe cost of labour, but their overall effect on employment is partially offset by the taxmeasures designed to generate alternative income to keep the benefits associated withthese contributions. Finally the suggestion is that the ideal scheme would be one thatprovides incentives for investment, focused towards employment-intensive sectors, atthe time that creates networks of social protection appropriate to deal with the problemsassociated with poverty.